2018
DOI: 10.1093/jas/sky288
|View full text |Cite
|
Sign up to set email alerts
|

Breed-specific differences in the immune response to lipopolysaccharide in ewes

Abstract: Innate immune response to a lipopolysaccharide (LPS) challenge varies among sheep breeds. How different breeds respond to bacterial infections impacts management practices of sheep producers. Hence, clinical response, acute-phase response, and gene expression of pro- and anti-inflammatory markers in peripheral white blood cells (WBCs) were examined after an LPS challenge in Dorset and Suffolk ewes. Ewes received either PBS or 2.5 µg/kg LPS (i.v.) 4 to 5 d after onset of synchronized estrus. Blood was collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…To reveal the mechanism of inflammatory disease and to find effective counter-measures for the chronic diseases, LPS, as a non-pathogenic immune activator, is being used to establish animal models. An intrajugular injection of 2.5 μg/kg LPS resulted in different expressions of inflammation-related genes in ewes [2]. Yates et al [27] reported that an intrajugular injection of 0.75 and 1.5 μg/kg LPS caused a dose-dependent inflammatory response, manifested as an increase in rectal temperature, serum cortisol, and serum insulin.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To reveal the mechanism of inflammatory disease and to find effective counter-measures for the chronic diseases, LPS, as a non-pathogenic immune activator, is being used to establish animal models. An intrajugular injection of 2.5 μg/kg LPS resulted in different expressions of inflammation-related genes in ewes [2]. Yates et al [27] reported that an intrajugular injection of 0.75 and 1.5 μg/kg LPS caused a dose-dependent inflammatory response, manifested as an increase in rectal temperature, serum cortisol, and serum insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Yates et al [27] reported that an intrajugular injection of 0.75 and 1.5 μg/kg LPS caused a dose-dependent inflammatory response, manifested as an increase in rectal temperature, serum cortisol, and serum insulin. A single injection of LPS in animals only induced a short-term acute immune stress, which caused a sharp increase in plasma concentrations of inflammatory cytokines that returned to the pre-injection levels after 4 to 8 h [2,27,28]. Therefore, to reduce the tolerance and avoid the risk of mortality due to LPS in lambs in the present study, an initial dose of 0.25, 1.25, or 2.5 μg/kg LPS was injected every other day with a dose increase of 20% each time to examine the putative effect of resveratrol on inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations